THE RELATIONSHIP BETWEEN STRATEGIC PLANNING AND CRISIS MANAGEMENT-A CASE STUDY AT SOUTHERN TECHNICAL UNIVERSITY - Ali Abdulzahra Adam (Galaxy International Interdisciplinary Research Journal, 2024)
This study aims to find out the relationship between the practice of strategic planning methods and crisis management at Southern Technical University. An explanatory sequential design was used, where unstructured interviews were conducted with experts and specialists to prepare a questionnaire, followed by structured interviews to interpret the results. A simple random sample was selected that targeted a group of employees at the upper and middle administrative levels. It amounted to 191 employees, and 181 valid questionnaires were retrieved for analysis. The data was analyzed using the (SPSS) program. The results showed a statistically significant effect of practicing strategic planning methods on crisis management among workers at these levels, and the level of practicing strategic planning methods was moderate. The field of business analysis ranked first in terms of the level of practicing strategic planning methods. The level of crisis management among workers was average, as the field of learning ranked first in terms of the level of crisis management. The study concluded that practicing strategic planning methods is important in enhancing the university’s ability to manage crises effectively. It also recommended that the Southern Technical University focus on improving the level of strategic planning and crisis management practice among its employees. In the context of the recommendations, the study indicated the need to organize training programs for employees on how to practice strategic planning methods in crisis management, provide the necessary resources to improve the level of crisis management among employees, and conduct more studies on the impact of strategic planning methods on crisis management in various institutions.